Projected sea-level contributions from tidewater glaciers are highly sensitive to chosen bedrock topography: a case study at Hansbreen, Svalbard - Möller, Marco; Navarro, Francisco; Huss, Matthias; id_orcid:0 000-0002-2377-6923; Marzeion, Ben (Cambridge University Press, 2023)
Calculation of the calving loss of tidewater glaciers depends on accurate bedrock information. In regional to global-scale projections of future tidewater glacier evolution this dependence is problematic. Bedrock topographies are often unknown and can only be modelled from surface properties. Existing approaches, however, mostly underestimate the ice thickness towards the calving fronts of marine-terminating glaciers. This implies a compromised performance of global-scale projection models which often employ functions of water depth at the calving fronts of tidewater glaciers. Here, we present a sensitivity study that analyses the impact of five different bedrock datasets on projected mass losses from the tidewater glacier Hansbreen in southern Svalbard. Our modelling study calculates the glacier's response to artificial mass-balance forcing. We show that bedrock inaccuracies may lead to a substantially deviating retreat behaviour. The common underestimation of frontal ice thickness/water depth in the modelled bedrock datasets induces an underestimation of sea level-relevant mass losses over the first several decades of modelling. The duration of this period is reduced when assuming warmer climates. Our results thus underline the importance of accurate bedrock topography data for the reliability of glacier evolution projections and for the accuracy of the temporal trajectories of related sea level-relevant mass losses. ISSN:0022-1430 ISSN:1727-5652